(untitled) (Indian Journal of Chemistry (IJC), 2024)
At present the incident of antimicrobial diseases, especially in immunological patients is life-long and growth the heath trouble. Growing difficulty of drug resistance has become a main concern for physicians. To deal with the problems of these antimicrobial diseases, amalgamation therapy has gained much interest. A new series of sulfonamides hybrids (3a-g) were synthesized by reaction of 4-aminoacetophenone with benzensulfonyl chlorides. To screened their antimicrobial and antimalarial activity with four bacteria, three fugal stains. Compounds 3d, 3e and 3c have excellent antibacterial activities with MIC values of 25, 50 and 62.5 respectively. The antimalarial activity of achieved derivatives 3a, 3d, 3e and 3f exhibited higher anti-antimalarial activity which Mean IC50 value is 0.70, 0.42, 0.74 and 0.82 respectively.